Pembuatan Keju Zea dengan Bahan Dasar Susu Jagung dan Telur Ayam Menggunakan Buah Ceremai dengan Uji Organoleptik - Yovita Harmiatun; Riska Septia Wahyuningtyas; Nisa Nadilla (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Cheese is a processed dairy product produced by coagulating mammalian milk, a process involving bacteria and enzymes (rennet). Cheese generally comes from mammals milk, such as goat, cow, and buffalo milk. The aim of this research was to determine the process of producing cheese from plant-based milk, namely corn and chicken eggs, using ceremai fruit as a coagulant with organoleptic tests. The cheese-producing process in this study involved three stages: producing corn milk, ceremai fruit filtrate, and cheese. Additionally, this study was expected to offer a solution to prevent stunting in toddlers and help pre-elderly individuals maintain muscle, bone, and dental health. This research was an experimental study with three repeated replications, and the data obtained were primary data from organoleptic tests by 25 respondents. The results of this study showed that the cheese product created the best zea cheese in terms of organoleptic characteristics. The highest preference scale from aroma, taste, and color indicators was Sampel K2 (50 ml corn milk, 50 ml chicken egg, and 50 ml of 50% ceremai fruit filtrate). Meanwhile, the highest preference scale for texture was Sampel K3 (50 ml corn milk, 50 ml chicken egg, and 50 ml of 25% ceremai fruit filtrate). This study concluded that the process of making zea cheese consisting of three groups was successful with the formation of curds (clumps) by the coagulant filtrate of ceremai fruit. The best sample that was most preferred from the organoleptic test was K2, which consisted of 50 ml of corn milk, 50 ml of chicken egg, and 50 ml of 50% ceremai fruit filtrate.